Quantum optics with ultracold quantum gases: Towards the full quantum regime of the lightmatter interaction - Mekhov, I; Ritsch, H (2012)
Although the study of ultracold quantum gases trapped by light is a prominent direction of modern research, the quantum properties of light were widely neglected in this field. Quantum optics with quantum gases closes this gap and addresses phenomena where the quantum statistical natures of both light and ultracold matter play equally important roles. First, light can serve as a quantum nondemolition probe of the quantum dynamics of various ultracold particles from ultracold atomic and molecular gases to nanoparticles and nanomechanical systems. Second, due to the dynamic lightmatter entanglement, projective measurement-based preparation of the many-body states is possible, where the class of emerging atomic states can be designed via optical geometry. Light scattering constitutes such a quantum measurement with controllable measurement back-action. As in cavity-based spin squeezing, the atom number squeezed and Schrödinger cat states can be prepared. Third, trapping atoms inside an optical cavity, one creates optical potentials and forces, which are not prescribed but quantized and dynamical variables themselves. Ultimately, cavity quantum electrodynamics with quantum gases requires a self-consistent solution for light and particles, which enriches the picture of quantum many-body states of atoms trapped in quantum potentials. This will allow quantum simulations of phenomena related to the physics of phonons, polarons, polaritons and other quantum quasiparticles. © 2012 IOP Publishing Ltd.